MEANINGFULNESS OF LIFE OF ELDERLY RESIDENTS OF RURAL AREAS - Kovalenko, Olena (PSYCHOLOGICAL JOURNAL, 2018)
The article is devoted to the problem of comprehension of the life of the elderly residents of rural areas (villagers). Residents of the rural area is a special socio-demographic group, which has its own age, socio-psychological features and social values, which are determined by the level of socio-economic and cultural development of a specific society. We characterized the social and age characteristics of older villagers. The scientific approaches to the problem of the meaning of life, its meaningfulness in old age are considered. Scientists emphasize that it is important for an older person to analyze and evaluate his life, and to preserve the meaning of life at the moment. The total number of participants took part in the study was 184 elderly people. The age of the participants was from 55 to 78 years. The average age of the subjects was 66.53 years. We used the test of meaningfulness orientation by Dmitriy Leontiev. Also we collected the information about some social features of elderly villagers through interviews. It is empirically confirmed that the elderly villagers lack the ability to comprehend their own lives and understand its meaning. Most of them have problems understanding the nature and orientation of their lives, which are largely due to changes in it. Old villagers are often dissatisfied with their today’s way of life and do not believe in their own ability to influence it; they live in their past. They are not always able to notice goals in the future, which make their lives meaningful and purposeful. Old villagers consider their life to be insufficiently interesting, emotionally rich and full of meaning. Many of them are not fully satisfied with the results of their past life. A minority of those who are relatively satisfied with the results of previous life have been identified. They perceive themselves as very strong personalities, who have a freedom of choice to build their lives in accordance with their own purposes and ideas about its meaning. Women have more faith in the possibility of such freedom compared to men. Old villagers are aware of the limited ability to control their lives and understand the influence of various factors on decision making and their implementation. Using the Student’s t-test it was confirmed that, firstly the level of meaningfulness of life in the elderly men and women who live in rural areas is not significantly different, although women perceive it emotionally more intense and have more plans for the future than men; secondly the lives of elderly villagers are less meaningful than the elderly inhabitants of cities. It has been established that the elderly villagers are most keen to change their way of life, living conditions. They also want to work, improve their financial position, solve problems with their relatives, etc.